THE JOGOKARIYAN RAMADHAN VILLAGE TRADITION AS A SYMBOL OF ISLAMIC DAKWAH AT THE JOGOKARIYAN MOSQUE (AN ANTHROPOLOGICAL STUDY) - Abdul Latif; Ahmad Raúf; Nurhadi Nurhadi; Muhammad Nur Najimi (Al-Qalam, 2026)
During the time of the Prophet Muhammad, mosques functioned as centers of worship, education, socialinteraction, and dakwah. Today, many mosques have narrowed their roles to ritual activities alone. TheJogokariyan Mosque in Yogyakarta, through its Jogokariyan Ramadan Village (Kampung RamadhanJogokariyan or KRJ) program, has emerged as a model for the contextual and community-basedrevitalization of mosque functions, yet it remains unstudied as a symbol of dakwah within the anthropologyof religion framework. This study analyzes the history and development of KRJ, its significance for thecommunity, and the dakwah symbols it manifests, grounded in the Qur'an Surah An-Nahl verse 125 andthe four means of dakwah. A descriptive qualitative method with a religious anthropology approach wasemployed. Data were collected through in-depth interviews, participant observation, and documentaryanalysis, and then analyzed using the Miles and Huberman model. Three principal findings emerged. First,Jogokariyan Mosque was established in 1966, and the 2025 KRJ marked its 21st iteration, having evolvedinto a large-scale Ramadan festival integrating religious, social, and economic dimensions. Second, KRJ carries social significance across four dimensions: volunteer empowerment, cultivation of compassion and tolerance, economic empowerment through the afternoon market, and transparent financial management.Third, KRJ embodies dakwah bil hikmah through accountable governance, mau'izhah hasanah throughinclusive iftar distribution, and mujadalah billati hiya ahsan through open social dialogue, while utilizingall four means of dakwah in an integrated manner. These findings affirm that KRJ is a mosque-baseddakwah model that harmoniously integrates spiritual, social, and economic dimensions into urban Muslimcommunity life.